2018
DOI: 10.1093/ecco-jcc/jjy044
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Classification of Postcolonoscopy Colorectal Cancers in Inflammatory Bowel Disease: A Dutch Population-Based Cohort Study

Abstract: In the IBDSL cohort, 45.0% of all CRCs were considered to be PCCRCs, mainly classified as missed lesions. Additionally, a large proportion of CRCs in our cohort were observed before a surveillance endoscopy was performed. Therefore, stringent adherence to IBD surveillance guidelines, improving endoscopy techniques and adjusting the surveillance program may lead to a decrease in CRC incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…colonoscopy until their last surveillance colonoscopy, colectomy, or CRC diagnosis, and estimated an incidence rate of 0.7 per 1000 years of follow-up [19]. Similarly, Wintjens et al reported a low PCCRC incidence rate of 0.39 per 1000 years of follow-up among 2801 IBD patients from the Netherlands [16]. Despite different PCCRC definitions, our CIPs are in line with those previously reported.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…colonoscopy until their last surveillance colonoscopy, colectomy, or CRC diagnosis, and estimated an incidence rate of 0.7 per 1000 years of follow-up [19]. Similarly, Wintjens et al reported a low PCCRC incidence rate of 0.39 per 1000 years of follow-up among 2801 IBD patients from the Netherlands [16]. Despite different PCCRC definitions, our CIPs are in line with those previously reported.…”
Section: Discussionsupporting
confidence: 88%
“…confirmed these findings [14]. It has been suggested that the elevated 3-year PCCRC rates in IBD patients stem from an increased likelihood of overlooking CRC and precancerous polyps, from aggressive biology leading to rapid CRC development, or are due to poor adherence to colonoscopy surveillance [16,17]. However, other explanations are possible.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…These data, along with our findings, suggest that VLCDCA 28:4 is maintained at a homeostatic level in the bloodstream and that decrements in the levels of this anti-inflammatory lipid can result in the development of CRC. Inflammation plays an important role in the development of malignancies, such that Inflammatory Bowel Disease (IBD) [14] and Irritable Bowel Syndrome (IBS) [15], are associated with an increased risk of developing CRC, while aspirin [16] and non-aspirin NSAIDs [17] have been shown to decrease the risk of developing CRC. However, the CRC patient population is an heterogeneous group, since CRC can develop via different biochemical pathways.…”
Section: Discussionmentioning
confidence: 99%